Office spirometry — indications and limitations - J.A. Richards (South African Family Practice)
Spirometry is the simplest test with which to evaluate respiratory function. Factors limiting the clinical usefulness of office spirometry relate mainly to the quality of the test. Accurate and reliable results depend on accurate equipment, a competent operator, a cooperative patient, a good quality control programme and appropriately selected reference values. Poorly performed spirometry increases the risk of misinterpreting the results.